How do remittances influence the mitigation of energy poverty in Latin America? An empirical analysis using a panel data approach - María Gabriela González Bautista; Eduardo Zurita Moreano; Juan Pablo Vallejo Mata; Magda Francisca Cejas Martinez (Economies, 2023)
Energy poverty represents a critical challenge in Latin America today, given the social disparities the region faces. In this context, this study focuses on exploring the effects of remittances on the energy poverty of 13 Latin American countries during the period 2000-2020. Panel estimations with fixed and random effects, along with the generalized method of moments, are employed to address potential endogeneity issues. The results suggest that remittances play a significant role in mitigating energy poverty in the Latin American region, particularly in rural areas. Furthermore, it is observed that economic growth and financial development act as mediators, allowing remittances to indirectly contribute to mitigating energy poverty. Although inequality was examined as a potential mediator, the findings suggest that it does not play a significant role in this context. It is concluded that remittances are an appropriate mechanism to improve the quality of life of the population, and their impact is strengthened in a more robust economic environment.
Keywords: 330; remittances; energy poverty; economic growth; international migration